2007
DOI: 10.3171/ped-07/12/474
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation of cerebrospinal fluid shunt failure and definition of instability among shunt-treated patients with hydrocephalus

Abstract: New patients with hydrocephalus can expect to undergo between two and four operations for insertion or revision of CSF shunts in the first 10 years after diagnosis. Patients who undergo more than 15 shunt operations in 10 years are statistical outliers. A focused study of such patients may yield useful suggestions for complication avoidance and improvement in the quality of life of children with hydrocephalus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The "flattening" of the ETV survival curve around 6 months contrasts with the pattern for shunt failure, which is one of continued failure over time. 1,3,15,16 Although ETV failure does occur beyond 6 months, it appears to be uncommon. 2 Thus, for a population of infants with parameters known to predict a chance of ETV failure that equals or even exceeds that for shunt failure, ETV may still be supported as the best initial treatment since virtually all failures will occur within this "safe window.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The "flattening" of the ETV survival curve around 6 months contrasts with the pattern for shunt failure, which is one of continued failure over time. 1,3,15,16 Although ETV failure does occur beyond 6 months, it appears to be uncommon. 2 Thus, for a population of infants with parameters known to predict a chance of ETV failure that equals or even exceeds that for shunt failure, ETV may still be supported as the best initial treatment since virtually all failures will occur within this "safe window.…”
Section: Discussionmentioning
confidence: 99%
“…The probability of shunt malfunction in the first year after placement and subsequently over time is universally recognized. 15,16 If, however, the likelihood of failure for primary treatment with ETV in a particular child were known to exceed that expected for shunting, then a shunt may be the optimal choice.Based on our large patient population in Uganda, we initially showed that an age younger than 1 year at time of treatment and the absence of visible evidence of flow across the ETV stoma at the time of surgery each significantly correlated with ETV failure. 20 It was later shown that adding bilateral lateral ventricle CPC to the procedure increased the likelihood of success in those younger Object.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15 Briefly, actuarial shunt survival data were developed in life-table format from a previously published institutional case series with exponential extrapolation to reach 216 months.…”
Section: Methodsmentioning
confidence: 99%
“…Piatt and Cosgriff 15 performed a digital simulation of the 10-year experiences of individuals with newly diagnosed hydrocephalus by using published shunt survival data. This exercise produced estimates of expected numbers of hospitalizations over the simulated study period with 95% and 99% confidence intervals.…”
mentioning
confidence: 99%